Biosynthesized CdS nanoparticles disturb E. coli growth through reactive oxygen production. (October 2019) - Nasrin, Tina; Patra, Mousumi; Escudey, Mauricio; Das, Tapan Kumar
Abstract: Aims: E. coli is a widely known model organism for life science research, especially in modern bio-engineering and industrial microbiology. The goal of our current study is to understand the growth inhibitory mechanism of biosynthesized CdS nanoparticles on E. coli bacteria . Main methods: Characterization of Aspergillus foetidus mediated CdS nanoparticles has been confirmed by Zeta potential, AFM and HRTEM analyses. Furthermore, we investigated the contribution of reactive oxygen species (ROS) and subsequently lipid peroxidation on the growth of E. coli . FACS and fluorometric studies were used to know the ROS production upon CdS nanoparticle treatment. Lipid peroxidation measurement was studied by thiobarbituric acid (TBA) assay. Key findings: The synthesized CdS nanoparticles are roughly spherical, poly-dispersed in nature and are in ~15 nm of size. Furthermore, our investigation confirmed that the cells treated with 200 μl of CdS nanoparticles produce about 50 % more ROS and about 5 times of lipid peroxidation over control cells. In addition, the number of E. coli colony survival and cell filamentation strongly depend on such lipid peroxidation caused by ROS, which actually produced due to the interaction with biosynthesized CdS nanoparticles in growth media. Significance: The current research would be helpful for the mechanistic understanding of growth inhibition of E. coli by CdS nanoparticle. This may be useful for industrial applications of E. coli like bacteria. Highlights: Aspergillus foetidus (MTCC8876) produce CdS nanoparticles from cadmium sulphate salt, having the size of ~15 nm. CdS nanoparticle has growth inhibitory activity towards E. coli bacteria. The growth inhibition occurred through the intracellular ROS-mediated membrane lipid peroxidation.